Syntactic features of proverbs in English and Uzbek languages (Texas Journal of Philology, Culture and History, 2024)
It is well known that a proverb is a short phrase that expresses deep wisdom of a nation who uses it. Genuine proverbs are sayings that have been mostly transmitted orally or through writing from one generation to the next. A proverb is a part of phraseology in most cases. This article discusses main features of proverbs in English and Uzbek languages comparatively